The marine sponge Agelas citrina as a source of the new pyrrole–imidazole alkaloids citrinamines A–D and N-methylagelongine - Cychon, Christine; Lichte, Ellen; Köck, Matthias (Beilstein Journal of Organic Chemistry, 2015)
The chemical investigation of the Caribbean sponge Agelas citrina revealed four new pyrrole–imidazole alkaloids (PIAs), the citrinamines A–D (1–4) and the bromopyrrole alkaloid N-methylagelongine (5). All citrinamines are dimers of hymenidin (6) which was also isolated from this sponge as the major metabolite. Citrinamines A (1) and B (2) are derivatives of the PIA dimer mauritiamine (7), whereas citrinamine C (3) is derived from the PIA dimer nagelamide B (8). Citrinamine D (4) shows an uncommon linkage between the imidazole rings of both monomeric units as it is only observed in the benzocyclobutane ring moiety of benzosceptrins A–C (9–11). Compound 5 is the N-methyl derivative of agelongine (12) which consist of a pyridinium ring and an ester linkage instead of the aminoimidazole moiety and the common amide bond in PIAs.
Keywords: Agelas citrina; marine sponges; mauritiamine; NMR; pyrrole–imidazole alkaloids